2016
DOI: 10.1007/s00425-016-2501-y
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous nitric oxide improves sugarcane growth and photosynthesis under water deficit

Abstract: Nitric oxide (NO)-mediated redox signaling plays a role in alleviating the negative impact of water stress in sugarcane plants by improving root growth and photosynthesis. Drought is an environmental limitation affecting sugarcane growth and yield. The redox-active molecule nitric oxide (NO) is known to modulate plant responses to stressful conditions. NO may react with glutathione (GSH) to form S-nitrosoglutathione (GSNO), which is considered the main reservoir of NO in cells. Here, we investigate the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
60
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 60 publications
3
60
0
3
Order By: Relevance
“…Such increase in root growth was associated with higher NO content (Fig. 6b), as found by Silveira et al (2016). At maximum water deficit, high NO synthesis was found in the root meristematic zone of plants supplied with 100% NO 3 − (Suppl.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Such increase in root growth was associated with higher NO content (Fig. 6b), as found by Silveira et al (2016). At maximum water deficit, high NO synthesis was found in the root meristematic zone of plants supplied with 100% NO 3 − (Suppl.…”
Section: Discussionsupporting
confidence: 68%
“…The root system is able to perceive low water availability and to produce chemical signals that regulate the water flow from roots to shoots. NO is one of those chemical signals that stimulates root expansion and development (Xu et al , 2017; Silveira et al , 2016). Given the effects of NO on root growth, it is reasonable to assume a potential influence of NO mediating auxin signaling in roots.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a signaling molecule, NO participates in several plant processes, including growth, respiration and photosynthesis, in addition to playing an important role in the responses of plants to biotic and abiotic stresses (Sami et al ). During WD, NO has been shown to promote root growth (Silveira et al ), increase the concentration of enzymatic and nonenzymatic antioxidants (Silveira et al ) and stomatal closure (together with abscisic acid; Joudoi et al ). Indeed, pretreatment with NO donors usually prepares plants for future stresses either by stimulating the antioxidant machinery or by inducing the production of endogenous NO, which in turn induces a series of additional events even after removal or degradation of the original NO donor (Santisree et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have clearly demonstrated the involvement of NO in mitigating the damage caused by WD, many questions remain unanswered. Most studies relate increased drought tolerance with the ability of NO to increase antioxidant defenses and to reduce the stomatal aperture (Santisree et al , Silveira et al , , Sami et al ) without considering its possible effects on hydraulic properties of the plant or the structural characteristics involved in the gas exchange. Indeed, studies that address the involvement of NO in the determination of g s have neglected the fact that, in addition to the degree of stomatal opening, maximum stomatal conductance can be determined by the morphological characteristics of stomata, like the stomatal size and density (Galmés et al ).…”
Section: Introductionmentioning
confidence: 99%